Integrating Project-Based and Collaborative Learning Management to Foster the Pancasila Student Profile at State Junior High School 8 Satap Alla - Salbi Salbi; Hasbi Hasbi; Masruddin Masruddin (International Journal of Educational Administration, Management, and Leadership, 2024)
This study investigates how project-based and collaborative learning management is integrated into the Pancasila Student Profile at State Junior High School 8 Satap Alla, a remote public school in South Sulawesi, Indonesia. The research aims to describe the implementation of integrated project-based and collaborative learning, identify the challenges encountered, and analyse its impact on students’ character formation. A qualitative descriptive case study design was employed, with data collected through classroom observations, semi-structured interviews with teachers, school leaders and students, as well as document analysis of lesson plans and school policies. Data were analysed using thematic procedures involving data condensation, display and conclusion drawing. The findings show that project-based and collaborative learning has been institutionalised into a three-stage cycle of planning, implementation and evaluation–reflection, in which teachers design contextual projects, facilitate active group work and guide students’ reflective review of their learning processes. The implementation, however, faces interrelated challenges in teacher readiness, uneven student participation and limited facilities that require continuous adaptation of project design and classroom management. Despite these constraints, the integrated approach contributes positively to the development of key dimensions of the Pancasila Student Profile, particularly collaboration (gotong royong), critical and creative thinking and learner independence, although these character outcomes are still emerging unevenly across different students and groups. The study concludes that sustained support for teacher professional development, student collaboration skills and school infrastructure is needed to optimise the transformative potential of project-based and collaborative learning in similar rural contexts.